Transition of Metabolisms in Living Popular Bark from Growing to Wintering Stages and Vice Versa: Changes in Glucose 6-Phosphate and 6-Phosphogluconate Dehydrogenase Activities and in the Levels of Sugar Phosphates - Sagisaka, Shonosuke (1974)
Activities of glucose 6-phosphate, 6-phosphogluconate, and isocitrate dehydrogenases, together with intermediate levels of the glycolytic pathway and the pentose phosphate cycle, were measured throughout a year in the living bark of poplar (Populus gelrica). Shoots, immediately after budding (early May), contained very high levels of the three enzyme activities, which fell gradually by early or mid-July to a level, roughly equivalent to budding (May) or growing (July) 2-year-old twigs. In September, the former two dehydrogenase activities of the new shoots and 2-year-old twigs began to rise, while the latter activity started to decrease. The rise of the two dehydrogenase activities continued until late November (or early December). The high level of the two dehydrogenase activities lasted until early in April of the following year and then the decrease in the activities began prior to the onset of budding, reaching a low, basal level in early May. The profile of changes in the two dehydrogenase activities appeared to coincide with the increase and decrease of soluble proteins. Normal concentrations of total hexose phosphates in the glycolytic pathway plus 6-phosphogluconate were found to be 288 to 895 μmoles/kilogram dry weight. During the metabolism transition (September and April), a transient and striking increase of 6-phosphogluconate was observed. In September, 6-phosphogluconate reached a level on the order of 10(−4)m and was 4 times that of fructose 6-phosphate. The increase in 6-phosphogluconate coincided with the increase in the glucose 6-phosphate dehydrogenase activity. Coincidentally, with the change of 6-phosphogluconate level, a large deviation of the in vivo ratio of fructose 6-phosphate to glucose 6-phosphate from the known equilibrium constant was observed, showing the relation of pentose phosphate cycle enzyme activity to the control of glycolysis. The ratio of glucose 6-phosphate to glucose 1-phosphate deviated from that predicted. These ratios fluctuated throughout the year and were affected by the growth phases. The levels of pentose phosphate cycle metabolites, except for 6-phosphogluconate, in the bark were extremely low. The level of inorganic phosphate in the living bark throughout the year was dependent upon the growth phases, suggesting the presence of a regulatory mechanism to maintain inorganic phosphate at a given level as the growth phase changed. Sugar phosphate levels of popular twigs or potato tubers (Solanum tuberosum) remained constant after they were stored for 2 weeks at low temperatures, whereas in sweet potato roots (Ipomoea batatas), the level rose to about 9-fold of the control, indicating the presence of a strict regulatory system for the synthesis and catabolism of sugar phosphate in the former two.